Monomorphic Ventricular Tachycardia as a Presentation of Giant Cell Myocarditis. (19th June 2019) - Chiu, Michael H.; Trpkov, Cvetan; Rezazedeh, Saman; Chew, Derek S.
Abstract : Background . Idiopathic giant cell myocarditis (GCM) has a fulminant course and typically presents in middle-aged adults with acute heart failure or ventricular arrhythmia. It is a rare disorder which involves T lymphocyte-mediated myocardial inflammation. Diagnosis is challenging and requires a high index of suspicion since therapy may improve an otherwise uniformly fatal prognosis. Case Summary . A previously healthy 54-year-old female presented with hemodynamically significant ventricular arrhythmia (VA) and was found to have severe left ventricular dysfunction. Cardiac MRI demonstrated acute myocarditis, and endomyocardial biopsy showed giant cell myocarditis. She was treated with combined immunosuppressive therapy as well as guideline-directed medical therapy. A secondary prevention implantable cardioverter defibrillator (ICD) was implanted. Discussion . GCM is a rare, lethal myocarditis subtype but is potentially treatable. Combined immunosuppression may achieve partial clinical remission in two-thirds of patients. VA is common, and patients should undergo ICD implantation. More research is needed to better understand this complex disease. Learning Objectives . Giant cell myocarditis is an incompletely understood, rare cause of myocarditis. Patients present predominately with heart failure and dysrhythmia. Diagnosis is confirmed by histopathology, and immunosuppression may improve outcomes. ICD implantation should be considered. In the absence of treatment, prognosis is poor with a median survival of three months.